Step
*
2
1
1
of Lemma
replace-seq-from-member-enum
1. f : ℕ ⟶ 𝔹@i
2. m : ℤ@i
3. ¬m < 1
4. [%1] : 0 < m@i
5. (replace-seq-from(f;m - 1;tt) ∈ enum-fin-seq(m - 1))
⊢ (λx.if x=m - 1 then f x else (replace-seq-from(f;m - 1;tt) x)
    ∈ map(λs,x. if x=m - 1 then tt else (s x);enum-fin-seq(m - 1))
   @ map(λs,x. if x=m - 1 then ff else (s x);enum-fin-seq(m - 1)))
BY
{ ((Assert ⌜f (m - 1) = tt ∨ f (m - 1) = ff⌝⋅ THENA Auto)
   THEN D (-1)
   THEN (BLemma `implies_l_member_append` THENA Auto)) }
1
1. f : ℕ ⟶ 𝔹@i
2. m : ℤ@i
3. ¬m < 1
4. [%1] : 0 < m@i
5. (replace-seq-from(f;m - 1;tt) ∈ enum-fin-seq(m - 1))
6. f (m - 1) = tt
⊢ (λx.if x=m - 1 then f x else (replace-seq-from(f;m - 1;tt) x)
    ∈ map(λs,x. if x=m - 1 then tt else (s x);enum-fin-seq(m - 1)))
∨ (λx.if x=m - 1 then f x else (replace-seq-from(f;m - 1;tt) x)
    ∈ map(λs,x. if x=m - 1 then ff else (s x);enum-fin-seq(m - 1)))
2
1. f : ℕ ⟶ 𝔹@i
2. m : ℤ@i
3. ¬m < 1
4. [%1] : 0 < m@i
5. (replace-seq-from(f;m - 1;tt) ∈ enum-fin-seq(m - 1))
6. f (m - 1) = ff
⊢ (λx.if x=m - 1 then f x else (replace-seq-from(f;m - 1;tt) x)
    ∈ map(λs,x. if x=m - 1 then tt else (s x);enum-fin-seq(m - 1)))
∨ (λx.if x=m - 1 then f x else (replace-seq-from(f;m - 1;tt) x)
    ∈ map(λs,x. if x=m - 1 then ff else (s x);enum-fin-seq(m - 1)))
Latex:
Latex:
1.  f  :  \mBbbN{}  {}\mrightarrow{}  \mBbbB{}@i
2.  m  :  \mBbbZ{}@i
3.  \mneg{}m  <  1
4.  [\%1]  :  0  <  m@i
5.  (replace-seq-from(f;m  -  1;tt)  \mmember{}  enum-fin-seq(m  -  1))
\mvdash{}  (\mlambda{}x.if  x=m  -  1  then  f  x  else  (replace-seq-from(f;m  -  1;tt)  x)  \mmember{}  map(\mlambda{}s,x.  if  x=m  -  1
                                                                                                                                                        then  tt
                                                                                                                                                        else  (s  x);enum-fin-seq(\000Cm 
                                                                                                                                            -  1))
      @  map(\mlambda{}s,x.  if  x=m  -  1  then  ff  else  (s  x);enum-fin-seq(m  -  1)))
By
Latex:
((Assert  \mkleeneopen{}f  (m  -  1)  =  tt  \mvee{}  f  (m  -  1)  =  ff\mkleeneclose{}\mcdot{}  THENA  Auto)
  THEN  D  (-1)
  THEN  (BLemma  `implies\_l\_member\_append`  THENA  Auto))
Home
Index